2007
DOI: 10.1038/nature06401
|View full text |Cite
|
Sign up to set email alerts
|

Optical frequency comb generation from a monolithic microresonator

Abstract: Optical frequency combs [1,2,3] provide equidistant frequency markers in the infrared, visible and ultra-violet [4,5] and can link an unknown optical frequency to a radio or microwave frequency reference [6,7]. Since their inception frequency combs have triggered major advances in optical frequency metrology and precision measurements [6,7] and in applications such as broadband laser-based gas sensing [8] and molecular fingerprinting [9]. Early work generated frequency combs by intra-cavity phase modulation [1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
1,275
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,930 publications
(1,328 citation statements)
references
References 41 publications
17
1,275
1
3
Order By: Relevance
“…This precision measurement allows to determine the dispersion of optical microcavity modes by exploiting all advantages of the spectroscopy scheme discussed before. Recently, it has been shown that ultra-high-Q microcavities allow to generate frequency combs with a bandwidth of more than 500 nm via four-wave mixing [13,14,15]. The total bandwidth of these combs is limited by the dispersion of the microcavity, which render the resonator modes nonequidistant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This precision measurement allows to determine the dispersion of optical microcavity modes by exploiting all advantages of the spectroscopy scheme discussed before. Recently, it has been shown that ultra-high-Q microcavities allow to generate frequency combs with a bandwidth of more than 500 nm via four-wave mixing [13,14,15]. The total bandwidth of these combs is limited by the dispersion of the microcavity, which render the resonator modes nonequidistant.…”
Section: Resultsmentioning
confidence: 99%
“…Taking only the leading terms in (3) we can deduce a rather crude analytical approximation for ℓ which ignores additional dispersion in very flattened spheroids with large a: A more intuitive way to specify the dispersion of a microresonator pertaining to optical frequency comb generation via four-wave mixing [13] is the mismatch between the generated comb modes ν comb and the respective microcavity modes ν ℓ (with ℓ being the angular mode number). Assuming that the central comb mode correponds to a certain microresonator mode at frequency ν ℓ0 , the frequency mismatch is given by…”
Section: Figmentioning
confidence: 99%
“…Microresonator-based Kerr comb sources [19,20] intrinsically offer unique advantages such as small footprint, large number of narrow-linewidth optical carriers, and line spacings of tens of GHz, which can be designed to fit established WDM frequency grids. However, while these advantages were recognized, previous transmission experiments [15] were limited to aggregate line rates of 1.44 Tbit/s due to strong irregularities of the optical spectrum associated with the specific Kerr comb states.…”
mentioning
confidence: 99%
“…In order to generate optical frequency combs (OFCs), the use of passive nonlinear cavities has been shown to represent an attractive alternative to traditional techniques based on femtosecond mode-locked lasers. Indeed, comb generation has been demonstrated to occur in continuosly pumped resonators with third-or second-order nonlinearities [1,2]. In cavities dominated by the second-order nonlinerity, OFCs can be generated when the nonlinear crystal is phase-matched for second harmonic generation and the cavity is pumped above the threshold of the so-called internally-pumped optical parametric oscillation [2,3].…”
Section: Maurizioderosa@inoitmentioning
confidence: 99%